Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting, November 23, 2015. (Policy Papers; Policy Paper ;, 2015)
The Managing Director's Global Policy Agenda (GPA) presented to the IMFC last month highlights the challenges associated with a rapidly changing and uncertain world. The limited room for policy maneuver and the need to adapt to new realities pose difficult trade-offs between supporting demand and current activity, reducing financial risks as financial conditions tighten, and implementing needed structural reforms to revive growth. Against this backdrop the GPA called to support growth today, invest in resilience and safeguard financial stability, improve the sustainability of the public finances, implement the structural reforms needed for sustainable and inclusive medium-term growth, and secure the effectiveness of the 2010 reforms. This document translates the policy priorities and strategic directions laid out in the Fall 2015 GPA and the IMFC communique into an Executive Board agenda for the next twelve months. The key focus of this agenda is to continue to refine and adapt the Fund's core activities?surveillance, lending, and capacity building?to the challenges faced by member countries. The 2015 Work Program continues the implementation of the 2014 Triennial Surveillance Review (TSR) recommendations and underpins a broader effort of the Fund to respond to the needs of the membership in an even more agile, integrated, and member-focused manner.